2002
DOI: 10.1111/j.1151-2916.2002.tb00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Yttria‐Stabilized Zirconia Thin Films on Textured Silver Substrates by Chemical Vapor Deposition

Abstract: The effect of deposition conditions on the growth of yttria‐stabilized zirconia (YSZ) films on textured silver substrates using the chemical vapor deposition (CVD) process was investigated. The crystalline structure of the YSZ film depended strongly on the deposition conditions, such as substrate temperature and deposition time. YSZ films prepared at 750°C using β‐diketone chelate sources, which had an orientation of c‐axis normal to the textured silver substrate surface. The YSZ surface was dense but not roug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…YSZ growth was mass-transfer limited above 827 • C and surface-reaction limited below 827-875 • C. This result was consistent with that of Kim et al [17] and Dubourdieu et al [24], who found the surface-reaction limited regime transitioned to the masstransfer limited regime above 740-770 • C. Growth rates reached a maximum between 827 and 875 • C, which was also consistent with the work of Pulver et al [13], Kim et al [17], Dubourdieu et al [24], and Jun et al [25], who observed a maximum in the YSZ growth rate at 770-840 • C. The activation energy of ∼51 kJ mol −1 determined from this work is also relatively close to the activation energies reported by Pulver et al [13] and Garcia et al [26] of 48 and 58 kJ mol −1 , respectively.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…YSZ growth was mass-transfer limited above 827 • C and surface-reaction limited below 827-875 • C. This result was consistent with that of Kim et al [17] and Dubourdieu et al [24], who found the surface-reaction limited regime transitioned to the masstransfer limited regime above 740-770 • C. Growth rates reached a maximum between 827 and 875 • C, which was also consistent with the work of Pulver et al [13], Kim et al [17], Dubourdieu et al [24], and Jun et al [25], who observed a maximum in the YSZ growth rate at 770-840 • C. The activation energy of ∼51 kJ mol −1 determined from this work is also relatively close to the activation energies reported by Pulver et al [13] and Garcia et al [26] of 48 and 58 kJ mol −1 , respectively.…”
Section: Discussionsupporting
confidence: 94%
“…: +1 865 574 6852; fax: +1 865 574 4913. alternative to EB-PVD and APS, with the added potential for better overall coverage as well as the ability to produce thick (>250 m), strain-tolerant, columnar coatings. Y(tmhd) 3 and Zr(tmhd) 4 (tmhd, 2,2,6,6-tetramethyl-3,5-heptanedianato, CH 3 -C(CH 3 ) 2 -C(=O)-CH 2 -C(=O)-C(CH 3 ) 2 -CH 3 ) precursors were chosen as source reagents because of their high solubility in most industrial solvents [11,12], and because of reported relatively high growth efficiencies (up to 35%) and moderate to high growth rates (10-50 m h −1 ) [7,8,[13][14][15][16][17][18]. The tmhd precursors can be used with an aerosol-assisted liquid delivery (AALD) method, which allow for continuous precursor introduction and effective evaporation.…”
Section: Introductionmentioning
confidence: 99%